Immersive technologies for engineering teaching: an approach applied to Higher Education - Jonathan Felipe da Silva; Sandro César Silveira Jucá; Solonildo Almeida da Silva (Revista Educar +, 2025)
The contemporary educational scenario demands constant updating in the face of technological innovations. In this context, traditional tools such as conventional whiteboards have been replaced by more modern resources, such as projectors and digital boards, which provide greater interactivity with the content being worked on, favoring the teaching-learning process. This study focuses on the analysis of the use of Augmented Reality (AR) as a pedagogical tool in the teaching of disciplines related to Mechanical Engineering. The proposal seeks to address a recurring difficulty among students: the limitation in the three-dimensional visualization of elements usually presented in two-dimensional representations. The methodology adopted is based on a bibliographic review of relevant works, with the aim of mapping the state of the art on the subject. The results obtained indicate the feasibility of implementing AR in the classroom, provided that there is prior training of teachers, who will act as mediators in the learning process. It is concluded that the use of AR contributes significantly to the improvement of teaching in the area of ​​Mechanical Engineering, promoting a broader and more effective understanding of the contents, in addition to presenting itself as a viable and applicable tool in the educational context.